Preparation of APP@CNCSi-DA and its application in intumescent flame retardant polypropylene - Minyi Liang; Caimin Feng; Jiali Jiang; Yanyan Nong; Jianguang Huang; Cuixia Lian; Yingpeng Huo; Yikun Zhang; Guoheng Wei; Zhihao He; Peihong Chen; Weibing Wu; et al. (Heliyon)
A Silicon-containing Oligomeric Charring Agent (CNCSi-DA) containing triazine rings and silicon was designed, synthesized and characterized. CNCSi-DA was chosen as macromolecular coating agent to modify Ammonium Polyphosphate (APP) to be core-shell coating-mixture (APP@CNCSi-DA). The synergistic effects of APP@CNCSi-DA on hydrophobicity, mechanical and flame retardant properties, and mechanism of flame-retardant polypropylene (PP) were studied. It was obvious that when the mass ration of APP to CNCSi-DA in APP@CNCSi-DA ranged from 15:15 to 0:30, the water contact angle meter (WCA) value of PP composites were higher than 90°. The CNCSi-DA reinforced the compatibility and improved the flexible and impact strength. APP@CNCSi-DA was highly effective in enhancing the flame retardancy of PP. When the weight ratio of APP to CNCSi-DA was 2:1 with 30 % content, the limited oxygen index (LOI) of the composite reached the peak of 35.9 %, which achieved UL-94 V-0. The IFR lowered flammability parameters significantly analyzed by cone calorimeter test.